2022
DOI: 10.3390/antiox11010111
|View full text |Cite
|
Sign up to set email alerts
|

Selenomethionine Ameliorates Cognitive Impairment, Decreases Hippocampal Oxidative Stress and Attenuates Dysbiosis in D-Galactose-Treated Mice

Abstract: The prevalence of age-related cognitive impairment is increasing as the proportion of older individuals in the population grows. It is therefore necessary and urgent to find agents to prevent or ameliorate age-related cognitive impairment. Selenomethionine (SeMet) is a natural amino acid occurring in yeast and Brazil nuts. It mitigates cognitive impairment in an Alzheimer’s disease mouse model, however, whether it works on age-related cognitive impairment remains unknown. In this study, SeMet significantly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Compared to the model group, the Ach content increased, and the AchE activity decreased in the FPF group ( P < 0.05). Similar to the results of Wang et al and Gao et al, treatment with FPF significantly inhibited AChE activity, effectively increased ACh levels, and ameliorated learning and memory impairment, suggesting that attenuating Ach and AChE dysregulation in the hippocampus was one of the strategies used by FPF to alleviate scopolamine-induced cognitive impairment.…”
Section: Resultssupporting
confidence: 83%
“…Compared to the model group, the Ach content increased, and the AchE activity decreased in the FPF group ( P < 0.05). Similar to the results of Wang et al and Gao et al, treatment with FPF significantly inhibited AChE activity, effectively increased ACh levels, and ameliorated learning and memory impairment, suggesting that attenuating Ach and AChE dysregulation in the hippocampus was one of the strategies used by FPF to alleviate scopolamine-induced cognitive impairment.…”
Section: Resultssupporting
confidence: 83%
“…The cognitive function was used to assess the effects of d -galactose administration. The study of Guo et al revealed that d -galactose administration increased oxidative stress and impaired cognitive function in mice . We found that d -galactose also caused a decrease in the NORT preference index in the A group.…”
Section: Discussionsupporting
confidence: 51%
“…On the one hand, the abundance of LPS-producing bacteria in the intestines (Bacteriaceae and Proteobacteria) was increased. On the other hand, SCFAs-producing bacteria, especially those that produce acetic acid and butyric acid were decreased in intestinal contents (Lachnospiraceae, Ruminococcaceae and Clostridia) (31,32). Intestinal defense is reduced, leading to the disruption of intestinal homeostasis, which adversely affects the host and exacerbates internal dysfunction in the host.…”
Section: Discussionmentioning
confidence: 99%